Lidocaine converts inducible ventricular fibrillation into sustained ventricular tachycardia in conscious dogs with recent myocardial infarction - Aidonidis, Isaac; Brachmann, Johannes; Rizos, Ioannis-Antonios; Toutouzas, P.; Kübler, Wolfgang (Cardiology, 1994)
The aim of the present study was to investigate the effect of lidocaine (L) on ventricular tachyarrhythmias with special reference to ventricular fibrillation (VF). Myocardial infarction (MI) was created in 39 dogs by doubly ligating the left anterior descending (LAD) coronary artery. All animals surviving the infarction (n = 33) were subjected to programmed ventricular stimulation 7.6 ± 3.2 days later. Local electrical activity was recorded from the subepicardium of the left ventricular wall by means of a specially designed composite electrode. L (2 and 4 mg/kg i.v.) facilitated the induction of sustained monomorphic ventricular tachycardia (sVT) in 8 dogs with nonsustained polymorphic ventricular tachycardia (nsVT) in the control. In 13 dogs developing sVT during control stimulation, L slowed the rate of tachycardia in 8 animals (first-dose effect), while it abolished arrhythmia induction in 5 animals (second-dose effect). It was interesting that L (2 mg/kg) abolished reproduction of control VF in 12 animals by converting it into sVT. L significantly depressed conduction and prolonged ventricular refractoriness in the infarction zone. The results suggest that L facilitates induction of sVT in conscious dogs with recent MI, thereby decreasing susceptibility of infarcted myocardium to aggressive polymorphic nsVT or VF. The capability of L to exacerbate slow conduction in the infarction zone seems not to favor the development of VF during this stage of MI.